Kepastian Hukum Atas Pemecahan Sertifikat Induk Tanah Terkait Developer Perumahan Yang Dinyatakan Pailit - Fernedy Fernedy; Yuhelson Yuhelson; Cicilia Julyani Tondy (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Real estate and housing remain persistent issues for many neighborhoods. There are still issues with the application of law in the realm of land ownership, and these issues frequently lead to disputes and conflicts. This study is a form of normative, doctrinal, or dogmatic legal inquiry. The study found that the buyer/consumer who has paid in full and made a deed of sale and purchase at the PPAT needs to look at the legal repercussions of the developer's failure to solve the certificate from two different angles: the developer's and the court's. While waiting for the certificate split process carried out by the curator as the responsible developer for the developer who has been declared bankrupt, and for consumers who have not yet completed payment on the house purchased from the developer, and only have PPJB, buyers can apply for a name transfer process at the land office. The consumer or buyer of the house whose solution has not been taken care of by the developer who is declared bankrupt can apply as a concurrent creditor so that the curator takes care of it and receives full compensation from the developer as represented by the curator or continues to manage the house. the homebuyer's or consumer's best interests. Since the house has not yet been completely paid off, the consumer/buyer of the house must also fulfill their commitments to pay off the remaining mortgage installments. Additional unfulfilled commitments include finishing the down payment on the developer-purchased home.